2022
DOI: 10.1186/s12951-022-01623-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting therapy and tumor microenvironment remodeling of triple-negative breast cancer by ginsenoside Rg3 based liposomes

Abstract: The chemotherapy effect of docetaxel (DTX) against triple-negative breast cancer (TNBC) remains mediocre and limited when encapsulated in conventional cholesterol liposomes, mainly ascribed to poor penetration and immunosuppressive tumor microenvironment (TME) caused by tumor stroma cells, especially cancer-associated fibroblasts (CAFs). Many studies have attempted to address these problems but trapped into the common dilemma of excessively complicated formulation strategies at the expense of druggability as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Additionally, the CCL5 levels were slightly reduced (Supplementary Figure S4H), whereas no consistent decrease was observed for the other cytokines (Supplementary Figure S4I). Moreover, many studies have reported that tumor cells can promote the activation of CAFs by secreting TGF‐β [25–28]. We hypothesized that TGF‐β plays an important role in the activation of CAFs, and the rescue experiments with exogenous TGF‐β further confirmed that SERPINE2 knockdown inhibited the activation of CAFs, while TGF‐β treatment rescued the above inhibitory effects (Figure 3G, Supplementary Figure S4J).…”
Section: Resultssupporting
confidence: 59%
“…Additionally, the CCL5 levels were slightly reduced (Supplementary Figure S4H), whereas no consistent decrease was observed for the other cytokines (Supplementary Figure S4I). Moreover, many studies have reported that tumor cells can promote the activation of CAFs by secreting TGF‐β [25–28]. We hypothesized that TGF‐β plays an important role in the activation of CAFs, and the rescue experiments with exogenous TGF‐β further confirmed that SERPINE2 knockdown inhibited the activation of CAFs, while TGF‐β treatment rescued the above inhibitory effects (Figure 3G, Supplementary Figure S4J).…”
Section: Resultssupporting
confidence: 59%
“…Furthermore, it has been reported that Rg3 has been demonstrated to revert activated cancer-associated fibroblasts (CAFs) to a quiescent state and reduce the dense stromal barrier by inhibiting the secretion of TGF-β from tumor cells and modulating the TGF-β/Smad signaling pathway. 16,64 Consequently, upon arrival at the tumor site, Rg3-PLGA@TMVs had the potential to decrease the levels of CAFs and collagen in the TME. As a result, it may promote the enhanced penetration of DOX and Rg3-PLGA@TMVs into the tumor and achieve TME remodeling.…”
Section: Papermentioning
confidence: 99%
“…9,10 Ginsenoside Rg3 is a natural compound in ginseng with a unique tetracyclic triterpene saponin structure. [11][12][13] It exhibits noteworthy anticancer properties, including the reduction of cancer metastasis and recurrence, 14 inhibition of tumor proliferation, 15,16 suppression of angiogenesis, 17 and promotion of tumor cell apoptosis. 18,19 As a result, it is frequently employed in clinical adjuvant chemotherapy to enhance treatment outcomes, alleviate the toxic side effects associated with chemotherapy drugs, and, most importantly, fortify the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through dual action of targeting tumor cells and remodeling the TME, to 90.3% of paclitaxel-resistant breast cancer cells are killed ( 55 ). In addition to paclitaxel, GS-Rg3-based liposomes can significantly enhance the antitumor effects of docetaxel in triple-negative breast cancer ( 56 ). Moreover, GS-Rg3-modified nanoparticles can enhance the immunogenic cell death (ICD) effect induced by doxorubicin ( 57 ).…”
Section: Antitumor Effects Of Gs-rg3mentioning
confidence: 99%